Lords of Contention Local Conflicts in the Cathedral Chapter of Manila in the Late Seventeenth Century - de la Rosa, Alexandre Coello (Philippine Studies: Historical and Ethnographic Viewpoints, 2021)
This article focuses on ecclesiastical contentiousness in the cathedral chapters (cabildos) in the seventeenth-century Philippines. First, it demonstrates the way in which intra-elite confrontations, negotiation, and local agency among church entities molded the city of Manila as a political arena. Second, it discusses Bishop Ginés de Barrientos’s (1681–1698) political unrest against the cabildo members, which demonstrate that disobedience was not the exception but the everyday rule. To reconstruct social fields set in motion in early modern Manila, this case study opens up a new conflict-ridden paradigm of religious division that stresses competition, contentiousness, and factionalism in the cathedral body.